Unveiling The Shadows: Exploring Child Abuse Incidence In Brunei’s Adult Population - Sulaiman, Noor Azimah; Mahalle, Salwa; Abdullah, Nor Zaiham Midawati (Pamomong: Journal of Islamic Educational Counseling, 2024)
The article describes a quantitative research study that examined the prevalence of abuse and neglect present in the life histories among a sample population in Brunei Darussalam. Data were gathered using the most standardized inventory in the field which was adapted to Bruneian context and used to measure incidents and types of abuse and neglect. A sample population of 112 participants drawn from two educational sites completed the Adverse Childhood Experiences International Questionnaire (ACE-IQ) with a 100% return data. The findings show that the most prevalence abuse and neglect among the participants were emotional and physical abuse as well as neglect. The study concludes that participants who reported any single form of abuse and neglect were likely to have suffered other types of abuse and neglect, and the most consistently strong correlations were between abuse of alcohol intoxication and several types of abuse, including sexual abuse with intercourse reported by the participants. The findings conclude that the most prevalence abuse was emotional abuse (91%), followed by physical and emotional neglect (59%) and physical abuse (46%). The lowest prevalence of abuse reported by the participants was sexual abuse (26%).